Jovenes Fotografos 1988. - Salaamadis, Madrid (Madrid : Instituto de la Juventud, 1988)
Teixidor, Anna Alemany ; David, Ramón ; Esteban, Javier ; Fortea, Canet ; Pérez, Alicia Estefania ; Carreira, Aida Fernández ; Garcia del Real, Eduardo ; González, Ramón Angel ; Guixa, Ricardo ; Mombiela, Lidia ; de Pablo, Montserrat ; Ribas, Christian ; Ruiz, Stefano ; Sánchez, Ignacio ; Vila I Alcalde, Jordi
Jovenes Fotografos 1988, Salaamadis, Madrid, 29 junio / 31 agosto 1988
boek